Epidemiology of injuries sustained by rear-seat passengers in frontal motor vehicle crashes. (March 2017) - Bose, Dipan; Crandall, Jeff; Forman, Jason; Longhitano, Douglas; Arregui-Dalmases, Carlos
Abstract: Objective: Advanced occupant protection systems in motor-vehicles (e.g., seat belts and airbags), while widely adopted for front-seat passengers, are either absent or offer disproportionally lower safety to rear-seat passengers in similar crashes. Optimization of advanced restraint systems for the rear-seat environment will require a detailed understanding of epidemiology and associated risk factors for injuries sustained by rear-seat passengers. Thus, the objective of the study is to use national level motor-vehicle travel and crash data to quantify rear-seat travel exposure, and determine the descriptive characteristics and the injury outcomes for rear-seat passengers involved in frontal collisions. Methods: While U.S. travel data from the 2009 National Household Travel Survey was used to determine rear-seat travel estimates, crash data from 2001 to 2010 National Automotive Sampling System Crash Worthiness Data System was used to enroll rear-seat passengers injured in a frontal crash. The descriptive epidemiology of rear-seat crash victims was separately done for the three age-groups: children (8–15 years old), adults (16–59 years old), and senior adults (60+). Results: The study indicated that senior adults in rear-seats were associated with a significantly higher rate of sustaining fatal (6%) and severe injuries (16% for MAIS 3+ injuries) in comparison to the younger cohorts. The distribution of severe injuries further indicated that the thorax was the most frequently injured region across all age groups irrespective of the belt-use status. Conclusions: Findings of the study conclude that while rear-seat travel in the U.S. is still very low and improving belt usage is a primary concern among rear-seat passengers; however, the epidemiology supports the need for adapting rear-seat restraint performance for effective protection for all groups of rear-seat passengers. Highlights: Thoracic injuries among rear-seat passengers is considerably higher than the front row counterparts. The senior adults in the rear-seat, in spite of their relatively higher belt usage rate, are significantly more vulnerable to serious injuries and fatalities in comparison to the younger age cohorts. It is necessary to adapt the existing restraint features to accommodate the priorities for the rear-seat occupant.